Tank deformation analysis by combining laser scanning and photogrammetry - Ali Al-Saedi; Fanar Abed; Imzahim Alwan (Engineering and Technology Journal)
Laser scanning systems are used to capture high-resolution 3D point clouds, thereby obtaining the object geometry. Terrestrial laser scanning (TLS) technology is an essential data capture tool for providing high-quality point clouds for industrial environments. However, TLS point clouds can be lacking and incomplete due to occlusions prevalent in complicated industrial environments. The static nature of the system makes it necessary to use a complementary data collection technique, such as cameras, to fill the gaps, enrich density, and improve data quality. Therefore, in this research, an integrated work frame was presented that would allow for the automatic and reliable direct co-registration of TLS data and photogrammetry of industrial objects. Combining TLS data and photogrammetric-derived SfM-MVS techniques makes getting a comprehensive dataset of complex objects possible. This is accomplished by employing individual approaches in situations that provide the most favorable conditions for operation. This research aims to detect deformation and determine the geometric features of oil plant equipment (tanks) in industrial sites. This was achieved by integrating TLS and UAV photogrammetry measurements of an oil plant in Basra City, Iraq. The gaps in the point cloud coverage introduced by TLS and UAV individual measurements are eliminated following the integration process. Detailed comparison analyses are performed on cross-sections, and the results are analyzed to show potential found to comply within a few millimeters. After data integration and accuracy analysis, the RMSE was withdrawn to reach 3 cm. This research approves the potential of data fusion to detect deformations in industrial sites.